Bioactive Coating of Ti6Al4V Lattices via Electrophoretic Deposition - Gurkan, Doruk; Sagbas, Binnur (SPRINGER, 2026)
Additive manufacturing (AM) enabled the production of complicated lattice architectures which found growing applications in biomedical implants because of their light weight, mechanical compliance, and potential to enhance osseointegration. Despite the advantages of lattice structures fabricated by additive manufacturing (AM) for biomedical implants, the improvement of bioactive coatings on these complex geometries remains an imposing challenge. Specifically, lattice topology's influence on coating quality and uniformity is poorly understood, leading to a knowledge gap that prevents achieving consistent and effective bioactive coatings on AM lattice structures. Furthermore, there is a need to perform research in optimizing these coatings for long-term bioactivity and durability in complex lattice geometries. This study is geared toward addressing this deficiency because it evaluates the effect of lattice topology on hydroxyapatite-chitosan composite coatings developed on laser powder bed fusion-manufactured (LPBF) Ti6Al4V lattice structures. The significance of EPD process parameters and the effect of lattice topology (dodecahedron, octahedron and star) on such parameter optimization were examined. The optimum EPD conditions resulted in more surface-covered and stable films. In the study where a total of 21 recipes were tested, quantitatively, the dodecahedron lattice structure in recipe 13 showed the highest cell viability of 92.7% and the lowest viability was achieved for the octahedron lattice structure in recipe 11 at 68.8%.. The results confirmed that lattice topology has an important influence on coating uniformity and morphology. The optimized EPD conditions produced coatings with improved surface coverage and stability.
Keywords: bioactive composite coating; coating parameters; electrophoretic deposition; laser powder bed fusion; lattice structures; HYDROXYAPATITE COATINGS; COMPOSITE COATINGS; BIOMEDICAL APPLICATIONS; CHITOSAN; PERFORMANCE; Materials Science